Decadent literature in twentieth-century Japan : spectacles of idle labor - Amano, Ikuho, 1967- (Palgrave Macmillan, 2013)
Decadence is a concept that designates a given historical moment as a phase of decay and valorizes the past as an irretrievable golden age. This study offers an innovative examination of a century of Japanese fiction through the analytical prism of decadence.